Parent Artery Reconstruction for Large or Giant Cerebral Aneurysms Using the Tubridge Flow Diverter: A Multicenter, Randomized, Controlled Clinical Trial (PARAT) - Liu, J.-m.; Zhou, Y.; Li, Y.; Li, T.; Leng, B.; Zhang, P.; Liang, G.; Huang, Q.; Yang, P.-f.; Shi, H.; Zhang, J.; Wan, J.; et al. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Although flow diverters have been reported with favorable clinical and angiographic outcomes in various literatures, randomized trials determining their true effectiveness and safety are still in lack. The Parent Artery Reconstruction for Large or Giant Cerebral Aneurysms Using the Tubridge Flow Diverter (PARAT) trial was designed to evaluate the safety and efficacy of the Tubridge flow diverter in the treatment of large or giant aneurysms in comparison with Enterprise stent-assisted coiling.MATERIALS AND METHODS: This prospective, multicenter, randomized trial was conducted at 12 hospitals throughout China. Enrolled adults with unruptured large/giant intracranial aneurysms were randomly assigned (1:1) to receive either Enterprise stent-assisted coiling or Tubridge flow diverter implantation. The primary end point was complete occlusion at 6-month follow-up, while secondary end points included technical success, mortality, target vessel–related stroke, aneurysm bleeding, in-stent stenosis, parent artery occlusion, and the frequency of all adverse events.RESULTS: Among 185 enrolled subjects, 41 withdrew before procedure initiation. Overall, 82 subjects underwent Tubridge implantation, and 62 subjects were primarily treated with stent-assisted coiling. The results of 6-month follow-up imaging included complete occlusion rates of 75.34% versus 24.53% for the Tubridge and stent-assisted coiling groups, respectively, with a calculated common odds ratio of 9.4 (95% confidence interval, 4.14–21.38; P < .001). There was a higher, nonsignificant frequency of complications for Tubridge subjects. Multivariate analysis showed a decreased stroke rate at the primary investigational site, with a marginal P value (P = .051).CONCLUSIONS: This trial showed an obviously higher rate of large and giant aneurysm obliteration with the Tubridge FD over Enterprise stent-assisted coiling. However, this higher obliteration rate came at the cost of a nonsignificantly higher rate of complications. Investigational site comparisons suggested that a learning curve for flow-diverter implantation should be recognized and factored into trial designs.FDflow diverterLTFlost-to-follow-upPARATParent Artery Reconstruction for Large or Giant Cerebral Aneurysms Using the Tubridge Flow DiverterSACstent-assisted coiling